HUBUNGAN ANTARA RELIGIUSITAS DENGAN KECEMASAN AKADEMIK PADA SISWA MADRASAH ALIYAH NEGERI - Fitri Ukhtia; Iredho Fani Reza; Zaharuddin Zaharuddin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Students often experience anxiety at the moment are in academic situations. This study examined the correlation between religiosity and academic anxiety in students MAN in one of the cities of Palembang. The independent variables in this study are religiosity, while the dependent variable is the academic anxiety. The hypothesis put forward is no relationship between religiosity and academic anxiety in students. The sampling technique in this study using a random cluster sampling technique which produces 319 students as respondents. Data collection methods used in this study a scale of religiosity that is made by researchers using the dimensions of religiosity based on the opinions Jamaluddin Ancok and Fuad Nashori Suroso consisting of five dimensions. Then the anxiety scale made by the academic researchers used a Hamilton anxiety symptoms based on the opinion that consists of 14 symptoms. Data analysis methods used to test the hypothesis of this research is simple regression analysis that generates a correlation coefficient of p = 0.000 (p <0.05), which showed a negative correlation between religiosity and academic anxiety in students. The results of the donations given to anxiety academic religiosity of 16.8% and the rest influenced by other factors not disclosed in this study.